Occurrence and risk assessment of zearalenone in flours from Portuguese and Dutch markets - Aldana, Juan Ramos (2014)
The occurrence of zearalenone (ZEA) in different flours for human consumption, from the Portuguese and Dutch markets, was evaluated. Good analytical performance was obtained through extraction with acetonitrile:water (90:10), clean-up with immunoaffinity columns, and detection and quantification by liquid chromatography-fluorescence detection. ZEA levels were determined in 48 samples to verify the compliance with the maximum permitted levels by European legislation. Two flour samples from Portugal exceeded the maximum limit established by EC. A major presence and levels in maize flours was shown. Coimbra (Portugal) and Utrecht (The Netherlands) samples showed that 37.5% of the samples were contaminated. Considering the percentage of TDI, ranging between 5.2 and 56%, the risk assessment linked with the exposure to ZEA was considered to be of concern for some studied populations, especially for babies. This is the first study on the intake assessment of ZEA present in different types of flour through their consumption.